2021
DOI: 10.1007/s00417-021-05188-y
|View full text |Cite
|
Sign up to set email alerts
|

Inter-eye relationship of intraocular pressure change after unilateral trabeculectomy, filtering canaloplasty, or PreserFlo™ microshunt implantation

Abstract: Purpose This study assesses short-term intraocular pressure (IOP) change in the fellow eye of glaucoma patients after mitomycin C–augmented trabeculectomy, filtering canaloplasty, or PreserFlo™ microshunt implantation in the treated eye. Materials and methods Retrospective chart review of 235 glaucoma patients (235 eyes) was performed. Patients underwent initial trabeculectomy (187 patients), filtering canaloplasty (25 patients), or PreserFlo™ microshunt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…There is no clear consensus in the peer-reviewed literature on the most efficacious dose and time of MMC to be used during this surgery. 22 In our study, 0.2 mg/mL MMC was used for 2 minutes as it has been done in previous studies, [10][11][12][13]16,20 because the scientific evidence to strongly recommend the use of higher concentrations of MMC in populations of European descent is still scarce. Previously reported data from a multicenter study conducted across multiple European sites by multiple surgeons using 2 different concentrations of MMC (0.2 and 0.4 mg/mL) 14 FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clear consensus in the peer-reviewed literature on the most efficacious dose and time of MMC to be used during this surgery. 22 In our study, 0.2 mg/mL MMC was used for 2 minutes as it has been done in previous studies, [10][11][12][13]16,20 because the scientific evidence to strongly recommend the use of higher concentrations of MMC in populations of European descent is still scarce. Previously reported data from a multicenter study conducted across multiple European sites by multiple surgeons using 2 different concentrations of MMC (0.2 and 0.4 mg/mL) 14 FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…4 The studies that have analyzed this device have shown different sample sizes (from 14 to 156 eyes) and follow-up times (1 wk-5 y). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In a recent major review, Bell et al 22 pointed out that the best available evidence regarding mitomycin C (MMC) dosing in combination with this device had been reported in the study carried out by Riss et al, 5 that compared 87 eyes with 2 concentrations of MMC (0.2 and 0.4 mg/mL) and locations (near and away from the limbus). The authors concluded that the trend was to increase the efficacy with higher concentrations of MMC placed close to the limbus.…”
mentioning
confidence: 99%
“…Clinical studies have previously reported previously that monocular treatments can affect fellow eyes,30–32 meaning that comparison of measures between treated and fellow eyes cannot serve as valid controls, and that population norms are the most useful comparators. Given that both the treated and fellow eyes showed a slower progression rate compared with previous reports, there may also be a similar sympathetic response in the fellow untreated eye.…”
Section: Discussionmentioning
confidence: 99%
“…Most fellow eyes in the 2 other groups did not show significant IOP change, however, IOP elevation occurred in 12.7% of all fellow eyes and it happened mostly on POD1, necessitating starting antiglaucoma medication in 2 eyes. 24 There is a complex intereye IOP relationship in different surgical procedures and the same is true upon using antiglaucoma medications, as 1 cannot expect the same IOP lowering effect by using an antiglaucoma agent in both eyes of 1 patient. 25 The mechanism for the COR is not well understood.…”
Section: Discussionmentioning
confidence: 99%